Application of the Seasonal Autoregressive Integrated Moving Average (SARIMA) Method to Forecast the Number of Vessel Passenger Departures tt Yos Soedarso Ambon Port - Butarbutar, Winda; Van Delsen, Marlon Stivo Noya; Djami, Ronald John (Tensor: Pure and Applied Mathematics Journal, 2023)
Maluku Province is a fairly large archipelago in Indonesia. The large number of islands which are the administrative areas of Maluku Province, encourages the creation of a supporting transportation system. Yos Soedarso Ambon Port is the largest port in Ambon. Based on the statistics of Indonesia, the number of ship passengers at Yos Soedarso Port in Ambon during the April 2023 period experienced an increase of 44.97 percent, while in the March 2023 period, it only experienced an increase of 42.94 percent. Because the data used is time series data and has a seasonal pattern, the most appropriate method for predicting the number of passengers is the Seasonal Autoregressive Moving Average (SARIMA) method. The SARIMA method is an approach model developed from the Autoregressive Moving Average (ARIMA) model used on time series or data with a seasonal pattern. This research produced the best model for forecasting the number of departures of ship passengers at Yos Soedarso Port, Ambon. With an MSE value of 26.44. with the shape of the model with MAPE 10.23%.